Epigenetic reprogramming in pancreatic premalignancy and clinical implications - Zhang, Wei; Jiang, Tingting; Xie, Keping (Frontiers in Oncology, 2023)
Pancreatic cancer (PC) is a most lethal human cancer with less than 10% five-year survival. Pancreatic premalignancy is a genetic and epigenomic disease and links to PC initiation. Pancreatic premalignant lesions include pancreatic intraepithelial neoplasia (PanIN), intraductal papillary mucinous neoplasm (IPMN) and mucinous cystic neoplasm (MCN), with pancreatic acinar to ductal metaplasia (ADM) as the major source of pancreatic premalignant lesions.Emerging evidence reveals that epigenetic dysregulation is an early event in pancreatic tumorigenesis. The molecular mechanisms of epigenetic inheritance include chromatin remodeling, modifications inhistone, DNA and RNA, noncoding RNA expression, and alternative splicing of RNA. Changes inthose epigenetic modifications contribute to the most notable alterations in chromatin structure and promoter accessibility, thus leading to the silence of tumor suppressors genes and/or activation of oncogenes. The expression profiles of various epigenetic molecules provide a promising opportunity for biomarkerdevelopment for early diagnosis of PC and novel targeted treatment strategies. However, how the alterations in epigenetic regulatory machinery regulate epigenetic reprogramming in pancreatic premalignant lesions and in different stages of their initiation needs further investigations. This review will summarize the current knowledge of epigenetic reprogramming in pancreatic premalignant initiation and progression, and its clinical applicationsas detection and diagnostic biomarkers and therapeutic targets in PC.